2021
DOI: 10.1029/2020pa004116
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Eocene Eastern Indian Ocean Dynamics Using Ocean‐Drilling Stratigraphic Records

Abstract: The Eocene Epoch is a 22 Myr long geologic time slice that is chiefly characterized by a long-term cooling trend, ultimately leading up to the transition from the greenhouse to the icehouse Cenozoic climate state. The Eocene starts with the Paleocene-Eocene Thermal Maximum (PETM, ∼56 Ma), a rapid carbon cycle perturbation that resulted in a ∼5°C global average temperature rise (Norris & Röhl, 1999; Tripati & Elderfield, 2005; Zeebe & Lourens, 2019). The PETM is followed by a series of similarly short-lived hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…Although previous studies have suggested that Site 762C sediments contain multiple hyperthermal horizons Thomas, 1992;Xu et al, 2021), the precise identification of hyperthermal events has not been achieved owing to the limited temporal resolution of previous bulk δ 13 C and δ 18 O records. Thus, the age model of Site 762C must be further considered.…”
Section: Revision Of the Age Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have suggested that Site 762C sediments contain multiple hyperthermal horizons Thomas, 1992;Xu et al, 2021), the precise identification of hyperthermal events has not been achieved owing to the limited temporal resolution of previous bulk δ 13 C and δ 18 O records. Thus, the age model of Site 762C must be further considered.…”
Section: Revision Of the Age Modelmentioning
confidence: 99%
“…We described the base of identifying each hyperthermal horizon on Supporting Text S2. As previous age models of Site 762C did not include the horizons of I1 and J events Thomas, 1992;Xu et al, 2021) and are based on not up-to-date magnetostratigraphic age, we updated the age model of Site 762C using newly identified hyperthermal horizons and revised magneto-and biostratigraphic ages by "Geologic Time Scale 2020 (GTS2020; Speijer et al, 2020)" and Westerhold et al (2020). The updated age-tie points are presented in Supporting Table S5.…”
Section: Revision Of the Age Modelmentioning
confidence: 99%
“…However, the utility and efficacity of the sedimentary noise models is still being explored. Hitherto, only few studies attempted to establish links between sealevel change and DYNOT and ρ1 models (Li et al, 2018a;Wang et al, 2020;Xu et al, 2021). While Li et al, 2018a dealt with Triassic marine sedimentary successions, Wang et al (2020) focused rather on a paleolake fillings across the Eocene-Oligocene transition.…”
Section: Application Of Sedimentary Noise Modeling For Sea-level Changementioning
confidence: 99%
“…In recent years, astrochronology has emerged as a pivotal method for constructing age models across diverse climatic records, including eolian, abyssal sediments, and continental sediments [4,[37][38][39][40][41]. The foundational theory of astronomical climate, proposed by Milutin Milankovitch in the early 20th century, has paved the way for the development of precise, high-resolution astronomical chronologies [42,43].…”
Section: Introductionmentioning
confidence: 99%